2015
DOI: 10.1152/ajpgi.00002.2015
|View full text |Cite
|
Sign up to set email alerts
|

Decreased melatonin secretion is associated with increased intestinal permeability and marker of endotoxemia in alcoholics

Abstract: . Decreased melatonin secretion is associated with increased intestinal permeability and marker of endotoxemia in alcoholics. Am J Physiol Gastrointest Liver Physiol 308: G1004-G1011, 2015. First published April 23, 2015; doi:10.1152/ajpgi.00002.2015.-Chronic heavy alcohol use is known to cause gut leakiness and alcoholic liver disease (ALD), but only 30% of heavy drinkers develop increased intestinal permeability and ALD. The hypothesis of this study was that disruption of circadian rhythms is a potential ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 50 publications
2
26
0
Order By: Relevance
“…Moreover, peak concentrations of TNF‐α and IL‐6 were positively correlated with melatonin levels, suggesting that low melatonin availability alters circadian gene expression in the early stages of sepsis, leading to changes in pro‐inflammatory cytokine release (Li et al , ). Depressed melatonin levels induced by alcohol use disorders are correlated with elevated intestinal permeability, LPS‐binding protein (a marker of endotoxaemia) and LPS, showing that the suppression of melatonin may promote gut leakiness and endotoxaemia (Swanson et al , ). But these findings require confirmation (Kawada, ).…”
Section: Melatonin and Sepsis In The Clinical Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, peak concentrations of TNF‐α and IL‐6 were positively correlated with melatonin levels, suggesting that low melatonin availability alters circadian gene expression in the early stages of sepsis, leading to changes in pro‐inflammatory cytokine release (Li et al , ). Depressed melatonin levels induced by alcohol use disorders are correlated with elevated intestinal permeability, LPS‐binding protein (a marker of endotoxaemia) and LPS, showing that the suppression of melatonin may promote gut leakiness and endotoxaemia (Swanson et al , ). But these findings require confirmation (Kawada, ).…”
Section: Melatonin and Sepsis In The Clinical Settingmentioning
confidence: 99%
“…LPS administration and sepsis also induce fatigue and decreased contractility of the ileum, urinary bladder and diaphragm, which can be attenuated or even reversed and returned to control levels by melatonin administration (Paskaloglu et al , ; Kurcer et al , ). Reduced melatonin levels are associated with increased intestinal permeability (Swanson et al , ). In such cases, melatonin administration attenuates apoptotic cell death in both intestinal epithelium and lamina propria (Ozdemir et al , ) and prevents LPS‐induced gastrointestinal disturbances (De Filippis et al , ).…”
Section: Protection Mediated By Melatonin Against Septic Injurymentioning
confidence: 99%
“…Twenty‐four studies reported on 29 statistically significant biomarkers and association with altered IP . Two studies reported that fasting glucose had a weak positive correlation with IP (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-four studies reported on 29 statistically significant biomarkers and association with altered IP. 10,23,25,32,35,[40][41][42][43][44][50][51][52][53][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] Two studies reported that fasting glucose had a weak positive correlation with IP 44,53 (Table 5). Moreover, an additional study reported that a plasma glucose level >5.7 nmol/L is associated with a greater odds of having altered IP (OR = 2.09; 95% CI: 2.09, 4.18; P = 0.036) in the general population 23 (Table 3).…”
Section: Biomarker Risk Factorsmentioning
confidence: 99%
“…Another negative aspect of kynurenine pathway activation is decreased conversion of tryptophan towards melatonin which besides its circadian rhythm regulating role, also has various immune-regulatory functions and has beneficial influence on intestinal permeability (157)(158)(159). Furthermore, it was demonstrated that increased intestinal LPS translocation in AIDS patients led to increased peripheral monocyte activation and increased trafficking into the brain, and it is believed that this mechanism contributes to HIV-associated dementia (160).…”
Section: Bacterial Lps Cause Depressive Symptomsmentioning
confidence: 99%